Tantangan Mahasiswa Generasi Z dalam Menjaga Nilai-nilai Islam di Era Digital: Challenges of Generation Z Students in Maintaining Islamic Values in the Digital Era - Atep Chairul Hikmat; Nisrina Keisha; Risyfa Wajdilmuna; Sharleen Ariani Ahnaf; Edi Suresman (Litera Academica Publishing, 2026)
Digital technological developments have significantly influenced the lives of Generation Z students, including their religious practices. This generation has grown up amidst the rapid advancement of the internet, social media, and access to information, which shape their mindset, behavior, and ways of interacting with religious values that indirectly influence the process of religious internalization. The close relationship with social media presents various challenges, such as the phenomenon of Fear of Missing Out (FOMO), pressure to follow trends, and exposure to global values that are not always aligned with Islamic teachings. These conditions potentially affect how students perceive and practice Islamic values in their daily lives. This study aims to analyze the various challenges faced by Generation Z students in maintaining Islamic values in the digital era and to identify efforts that can be made to address these challenges. The research employs a qualitative approach with a descriptive-analytical method through interviews and literature studies. Data were obtained from interviews with Generation Z students as well as reviews of various scientific sources, such as journals, books, and previous relevant studies. The findings indicate that strengthening digital literacy, increasing religious awareness, and utilizing technology wisely and selectively are important factors in maintaining the Islamic identity of students amidst the rapid development of digital technology. Digital technological developments have significantly influenced the lives of Generation Z students, including their religious practices. This generation has grown up amidst the rapid advancement of the internet, social media, and access to information, which shape their mindset, behavior, and ways of interacting with religious values that indirectly influence the process of religious internalization. The close relationship with social media presents various challenges, such as the phenomenon of Fear of Missing Out (FOMO), pressure to follow trends, and exposure to global values that are not always aligned with Islamic teachings. These conditions potentially affect how students perceive and practice Islamic values in their daily lives. This study aims to analyze the various challenges faced by Generation Z students in maintaining Islamic values in the digital era and to identify efforts that can be made to address these challenges. The research employs a qualitative approach with a descriptive-analytical method through interviews and literature studies. Data were obtained from interviews with Generation Z students as well as reviews of various scientific sources, such as journals, books, and previous relevant studies. The findings indicate that strengthening digital literacy, increasing religious awareness, and utilizing technology wisely and selectively are important factors in maintaining the Islamic identity of students amidst the rapid development of digital technology.